Analysis of the development of tourism infrastructure supporting the island of the karampuang in the regency of Mamuju - Sariang, G.N. (International Journal of Psychosocial Rehabilitation, 2020)
Karampuang Island with beautiful panorama and potential Karampuang Island has promised to become a natural tourist island with an area of about 6 Km² and has a population of 2,937 inhabitants offering natural tourism that is very enchanting especially its coral reefs but in this case it has not been handled optimally because it is still the unavailability of infrastructure (such as infrastructure) that can support and serve as an island natural tourism that can be enjoyed by tourists and can increase the Mamuju Regency APBD. The purpose of this study was to determine the infrastructure development efforts of Karampuang Island as a tourist attraction in Mamuju Regency and the factors that hamper it in carrying out development efforts. The theory in this study is Suwantoro's theory that the main elements that support the development of tourism, tourism objects and tourist attractions, tourism infrastructure, tourism facilities, governance or infrastructure and the community or the environment. This research uses descriptive qualitative research methods. Data collected through interviews, documentation and observation. The results of this study indicate that the infrastructure on Karampuang Island is still in the development stage and therefore still needs cooperation between related parties to continue this activity. Infrastructure that is deemed necessary to be developed to support tourism activities is clean water infrastructure, mobile networks and road access.